Great Big Agile : an OS for Agile Leaders - Dalton, Jeff (Apress, 2019)
"This book presents the Agile Performance Holarchy (APH)-- a "how-ability" model that provides agile leaders and teams with an operating system to build, evaluate, and sustain great agile habits and behaviors. The APH is an organizational operating system based on a set of interdependent, self-organizing circles, or holons, that reflect the empirical, object-oriented nature of agility. As more companies seek the benefits of Agile within and beyond IT, agile leaders need to build and sustain capability while scaling agility-- no easy task-- and they need to succeed without introducing unnecessary process and overhead. The APH is drawn from lessons learned while observing and assessing hundreds of agile companies and teams. It is not a process or a hierarchy, but a holarchy, a series of performance circles with embedded and interdependent holons that reflect the behaviors of high-performing agile organizations. Great Big Agile provides implementation guidance in the areas of leadership, values, teaming, visioning, governing, building, supporting, and engaging within an all-agile organization."--Page 4 of cover